Cooperative Learning Approach in Teaching and Learning Writing Skills: Practices and Challenges - Abheti, Mitiku Teshome; Beriso, Italo (IJET (Indonesian Journal of English Teaching), 2024)
The study was tried to investigate the practices and challenges of cooperative learning approach in teaching and learning writing skills of Grade 11 students, Afar Regional State, Logia Secondary and Preparatory School, in focus. More specifically, the study addressed the following research questions: (1) How is cooperative learning practiced in teaching and learning writing skills? (2) What are the challenges that hinder the effective implementation of cooperative learning in writing skills? The main subjects of the study were Grade 11 students of Logia Secondary and Preparatory School. Moreover, one of a social science classes were randomly selected. The data for this research purpose was collected through students’ questionnaire, teacher’s and students’ interview. Regarding the practices of CL in writing skills, both the teacher and students have positive attitudes i.e. teaching writing cooperatively improves students’ writing performance. Both the teacher and students believed that cooperative learning approach is practiced in their teaching and learning of writing somehow. Based on the data obtained from teacher’s interview and students’ questionnaire,  there are many challenges that resist the successful implementation of CL which could be grouped under student-related, teacher-related, classroom-related, time-related and weather condition-related problems. As of students’ questionnaire and interview, the fear of grammar, the writing itself and how to organize ideas together are some of the problems students face in learning writing skills. To keep the implementation more effective and to overcome the challenges, some recommendations were forwarded.